LOVE IN PRIDE AND PREJUDICE - Budiantie, Arina (2017)
Pride and Prejudice is a novel written by Jane Austen that is published in the United Kingdom in 1813, and it has been adapted to a movie with Joe Wright as the director. The movie itself was released in the United Kingdom in 2005. Pride and Prejudice tells about the love stories that are experienced by the characters, especially, Elizabeth Bennet, Jane Bennet, Charlotte, and Lidya Bennet. The theory used in this study is Sternberg's (1986) triangular theory of love. This theory is used to identify the kinds of love in which the characters Elizabeth, Jane, Charlotte, and Lidya are engaged in in the movie. Based on Sternberg's theory, six types of love have been identified to be experienced by the characters, namely (1) liking or friendship, (2) infatuated love, (3) empty love, (4) romantic love, (5) fatuous love, and (6) consummate love. The present study is expected to provide better insights into the subject of love.